2019
DOI: 10.1111/jcmm.14854
|View full text |Cite
|
Sign up to set email alerts
|

LASP1 promotes proliferation, metastasis, invasion in head and neck squamous cell carcinoma and through direct interaction with HSPA1A

Abstract: LIM and SH3 protein 1 (LASP1) is a specific focal adhesion protein that promotes metastasis in a variety of tumours. However, its role in head and neck squamous cell carcinoma (HNSCC) has not been fully validated. The purpose of this study was to analyse the interaction of LASP1 and its binding partner in HNSCC. The expression of LASP1 and HSPA1A in HNSCC was analysed by real-time PCR and Western blot.The effects of LASP1 on the biology behaviour of HNSCC cell lines were observed in vivo and in vitro. Co-immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Co-immunoprecipitation (Co-IP) analysis was performed as described in our previous study ( 16 ). Briefly, the cells were lysed with IP buffer (proteins at a concentration of 1 mg/mL) and incubated with antibodies against PLAU1 (1:20, Proteintech, China) or MMP1 (1:20, Abcam, UK) at 4°C overnight, followed by incubation with protein A/G Magbeads (Merck) at 4°C for 6 h. The proteins were then separated from the Magbeads by treatment at 105°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Co-immunoprecipitation (Co-IP) analysis was performed as described in our previous study ( 16 ). Briefly, the cells were lysed with IP buffer (proteins at a concentration of 1 mg/mL) and incubated with antibodies against PLAU1 (1:20, Proteintech, China) or MMP1 (1:20, Abcam, UK) at 4°C overnight, followed by incubation with protein A/G Magbeads (Merck) at 4°C for 6 h. The proteins were then separated from the Magbeads by treatment at 105°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Jakobsson et al analyzed 53 patients with high-grade serous ovarian cancer using a protein mass spectrometer and found that unmethylated HSPA1 may be a prognostic marker for high-grade serous ovarian cancer patients [36]. Chen et al analyzed the expression of LLIM and SH3 protein 1 (LASP1) and HSPA1A in head and neck squamous cell carcinoma (HNSCC) by quantitative PCR and Western blot, and found that LASP1 and HSPA1A were highly expressed in HNSCC and were associated with poor OS of HNSCC patients [37]. HSPA1A has not been reported in the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A co-immunoprecipitation (Co-IP) analysis was performed in our previous study. 20 In brief, the cells were lysed with IP buffer and incubated with the specific antibodies previously mentioned at 4°C overnight, followed by incubation with protein A/G Magbeads (Merck) for 6 h at 4°C. The proteins were separated from the beads for 10 min at 105°C.…”
Section: Co-immunoprecipitation Analysismentioning
confidence: 99%